Aerobic exercise: Bioenergetics, physiological adjustments, fatigue and performance indices Exercício aeróbio: Aspectos bioenergéticos, ajustes fisiológicos, fadiga e índices de desempenho - Caputo F. (2009)
The objective of this study was to present relevant updated information regarding the physiological determinants of aerobic training and performance. In contrast to common concepts, the aerobic metabolism rapidly responds to energy requirements, with the anaerobic and aerobic energy systems equally contributing to total energy production during maximal exercise lasting about 75 s. However, in the case of longer exercise duration the possible mechanisms of fatigue related to anaerobic metabolism are still the main determinants of exercise tolerance. Prolonged exercise (more than one hour) can be limited by several factors such as substrate depletion, water and electrolyte disturbance, or problems related to thermoregulation leading to an increase in body temperature. The most important variables of endurance performance have been organized into a model that integrates factors such as maximum oxygen uptake (VO2max), blood lactate thresholds, and muscle efficiency. For highly trained athletes, in addition to a high VO2max, success in endurance events also requires the ability to exercise for prolonged periods at a high percentage of VO2max, as well as to efficiently convert the energy produced into muscle work. Depending on the duration of the aerobic event, the training sessions should be aimed at improving VO2max, anaerobic lactate capacity and acidosis tolerance in the case of short-lasting events and aerobic capacity for events of intermediate duration, and at increasing muscle glycogen content and fat utilization in the case of long-lasting events.